2011
DOI: 10.1158/1078-0432.ccr-10-3024
|View full text |Cite
|
Sign up to set email alerts
|

Pentraxin-3 Is a Novel Biomarker of Lung Carcinoma

Abstract: Purpose: Our objective was to validate the performance of three new candidate lung cancer biomarkers, pentraxin-3 (PTX3), human kallikrein 11 (KLK11), and progranulin.Experimental Design: We analyzed by commercial ELISA, and with a blinded protocol, 422 samples from 203 patients with lung carcinoma, 180 individuals with high risk for lung cancer (heavy smokers), and 43 individuals with cancers other than lung. All samples were obtained from the Early Detection Research Network (Reference set A).Results: We fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 24 publications
4
92
1
Order By: Relevance
“…The potential role of PTX3 as a tissue and serum marker of carcinogenesis was recently postulated for human soft tissue liposarcoma (25) and lung carcinoma (20). Serum PTX3 elevation in patients with cancer are not well understood, but its known overexpression by endothelial cells and macrophages in response to inflammatory signals as well as its role in clearance of cells undergoing apoptosis (14) both suggest that PTX3 may act as a biomarker for neoplasia, through its elevation in the inflammatory microenvironment of the tumor and in the clearance of apoptotic cells (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential role of PTX3 as a tissue and serum marker of carcinogenesis was recently postulated for human soft tissue liposarcoma (25) and lung carcinoma (20). Serum PTX3 elevation in patients with cancer are not well understood, but its known overexpression by endothelial cells and macrophages in response to inflammatory signals as well as its role in clearance of cells undergoing apoptosis (14) both suggest that PTX3 may act as a biomarker for neoplasia, through its elevation in the inflammatory microenvironment of the tumor and in the clearance of apoptotic cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike short pentraxins, such as C-reactive protein (CRP), PTX3 is not produced by hepatocytes but synthesized by a variety of cell types at the site of inflammation (14,19), whereby it seems to regulate complement activation (14,17,18). Recent findings suggest an insidious relationship between complement and cancer in terms of cellular proliferation and regeneration as well as angiogenesis (18,20).…”
Section: Cd25mentioning
confidence: 99%
“…Because of the difficulty of confirming the roles of all Sp1-regulated genes identified by the microarray analysis, we examined proliferation-related genes that were potentially regulated by Sp1 to elucidate the contributions of Sp1-regulated genes to tumor growth. Among the 68 Sp1-regulated genes related to proliferation, seven genes, namely, Aldh3a1, Arg1,Cd9,Ptx3,Tacstd2,Tpx2, and Vav1, have been reported to be overexpressed in lung tumors or to be biomarkers for the diagnosis of lung cancer (Shimada et al, 2005;Ma et al, 2006;Moreb et al, 2008;Lazer et al, 2009;Rotondo et al, 2009;Kohmo et al, 2010;Diamandis et al, 2011). In addition, Ctsz, Il18, Il4ra, Lcn2, Ntrk3, and Ros1 have been shown to be involved in tumor growth and cancer pathogenesis (Wood et al, 2006;Todaro et al, 2008;Berger et al, 2010;Sevenich et al, 2010;Rovina et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic sensitivity of pentraxin at 100% specificity was found to be 68%. In a recent study, Diamandis et al [153] confirmed Pentraxin-3 but not KLK11 or progranulin as a new serum biomarker for lung carcinoma. Pentraxin-3 was able to discriminate lung cancer patients from high-risk controls with moderate sensitivity (37% at 90% specificity and 48% at 80% specificity), which was comparable to other currently used lung cancer biomarkers.…”
Section: Potential Of Lung Cancer Protein Biomarkersmentioning
confidence: 97%